Factors influencing medical tourism destination choice in Klang Valley, Malaysia / Nur Hazira Zulkifli and Aisyah Afifah Che Man - Zulkifli, Nur Hazira; Che Man, Aisyah Afifah (2013)
The purpose of this paper is to understand and analyse the factors that influencing tourists in choosing a destination for medical tourism in Malaysia. To achieve this research paper, the study examines the motivation of individuals to engage in medical tourism and certain criteria that will evaluate alternative medical tourism destination. As we know, Malaysia is one of best destination for tourists to do their treatment or medical. There are many reasons why Malaysia’s become the most popular destination for medical tourism. There are three main factors that influencing the destination choice of medical tourism which are towards price, high-quality of services and easy access medical alternatives. The study also examines the research objectives, problems statement which occur in previous research and also several limitations occur in this research. The limitation that occurs in this study is towards the risk of quality and safety, language barriers and also towards difficulty to determine how qualified a doctor in another country. This study also concludes the data analysis by using SPSS towards factors influencing medical tourism destination in Malaysia.